2004
DOI: 10.1073/pnas.0404101101
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of apoptosis in acute promyelocytic leukemia cells leads to increases in levels of oxidized protein and LMP2 immunoproteasome

Abstract: On reaching maturity, animal organs cease to increase in size because of inhibition of cell replication activities. It follows that maintenance of optimal organ function depends on the elimination of oxidatively damaged cells and their replacement with new cells. To examine the effects of oxidative stress and apoptosis on the accumulation of oxidized proteins, we exposed acute promyelocytic leukemia cells to arsenic trioxide (As 2O3) in the presence and absence of a general caspase inhibitor (benzyloxycarbonyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In previous studies, the correlation between the inhibition of apoptosis and protein carbonyl accumulation in response to indirect and direct effects of arsenic trioxide (As 2 O 3 ) and H 2 O 2 , respectively, was demonstrated in multicellular eukaryotic organisms (3). In this study, we demonstrated that the same phenomenon also exists in unicellular eukaryotic systems.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…In previous studies, the correlation between the inhibition of apoptosis and protein carbonyl accumulation in response to indirect and direct effects of arsenic trioxide (As 2 O 3 ) and H 2 O 2 , respectively, was demonstrated in multicellular eukaryotic organisms (3). In this study, we demonstrated that the same phenomenon also exists in unicellular eukaryotic systems.…”
Section: Resultssupporting
confidence: 68%
“…The possibility that inappropriate regulation or inhibition of apoptotic capacity might contribute to the aging process and to the development of some pathologies is underscored by the demonstration that inhibition of apoptosis in cultured mammalian acute promyelocytic leukemia-derived NB4 cells leads to a substantial increase in the accumulation of oxidized proteins (3). Both processes are characteristic of aging and many diseases (4).…”
mentioning
confidence: 99%
“…2) Taken together, the above results suggest that ROS overproduced by ortho-quinoid PAHs modify protein structure through destruction of the sulfhydryl moiety. 19,20) Several ortho-qunoid PAHs such as 9,10-PQ and 9,10-AQ are present in the atmosphere at the The concentration ratios of 1,2-NQ (ortho-type) to 1,4-NQ (para-type) in the atmosphere, gasolineand diesel-engine exhausts were respectively 0.25, 1.17 and 0.09, although the concentration ratio of ortho-type to para-type was not reported for the other quinoid PAHs. 21) These facts suggest the other ortho-quinoid PAHs might also exist in the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…These species increase mitochondrial membrane permeability, due to the alteration of membrane potential (ΔΨ) with release of cytochrome C, which activates caspases (cysteine-aspartic proteases involved in apoptosis, necrosis, and inflammation) with the final effect of inducing programmed cell death (apoptosis). Induction of apoptosis and accumulation of oxidized proteins have been observed by the treatment of cells with As 2 O 3 in the presence of inhibitors of caspase (Khan et al 2004). In addition the c-Jun N-terminal kinase (JNK) has been reported to be involved in apoptosis dependent from As 2 O 3 ; the latter one also activates the pro-apoptotic Bcl-2-associated X protein (Bax), a member of B-cell lymphoma 2 (Bcl-2) family (Fig.…”
Section: Claudetitementioning
confidence: 99%
“…It is noteworthy that arsenic trioxide was dissolved in concentrated aqueous solution of sodium hydroxide, followed by adjustment to biological pH value, in most of the reported experimental procedures (Park et al 2003a, b;Khan et al 2004;Shen et al 2004). However, it is known that arsenites are produced by treatment of As 2 O 3 with alkaline hydroxides, so that very probably the active arsenic species could not be the starting arsenic trioxide.…”
Section: Claudetitementioning
confidence: 99%